Recombinase polymerase amplification combined with lateral flow biosensor for rapid visual detection of Clostridium perfringens in chicken meat and milk - Tian, Rui; Xie, Feng; Liu, Yuqing; Liu, Guangjin; Li, Qingxia; Wang, Jinxiu; Zhang, Hongjian; Dai, Lei; Zhang, Wei (Frontiers in Veterinary Science, 2024)
Clostridium perfringens is one of the major anaerobic pathogen causing food poisoning and animal enteritis. With the rise of antibiotic resistance and the restrictions of the use of antibiotic growth promoting agents (AGPs) in farming, Clostridium enteritis and food contamination have become more common. It is time-consuming and labor-intensive to confirm the detection by standard culture methods, and it is necessary to develop on-site rapid detection tools. In this study, a combination of recombinase polymerase amplification (RPA) and lateral flow biosensor (LFB) was used to visually detect C. perfringens in chicken meat and milk.Two sets of primers were designed for the plc gene of C. perfringens, and the amplification efficiency and specificity of the primers. Selection of primers produces an amplified fragment on which the probe is designed. The probe was combined with the lateral flow biosensor (LFB). The reaction time and temperature of RPA-LFB assay were optimized, and the sensitivity of the assay was assessed. Several common foodborne pathogens were selected to test the specificity of the established method.Chicken and milk samples were artificially inoculated with different concentrations (1× 10 2 CFU/mL to 1× 10 6 CFU/mL) of C. perfringens, and the detection efficiency of RPA-LFB method and PCR method was compared.RPA-LFB can be completed in 20 min and the results can be read visually by the LFB test strips. The RPA-LFB has acceptable specificity and the lowest detection limit of 100 pg/μL for nucleic acid samples. It was able to stably detect C. perfringens contamination in chicken and milk at the lowest concentration of 1× 10 4 CFU/mL and 1× 10 3 CFU/mL, respectively.In conclusion, RPA-LFB is specific and sensitive. It is a rapid, simple and easy-to-visualize method for the detection of C. perfringens in food and is suitable for use in field testing work.